Clinicopathological features of breast cancer without mammographic findings suggesting malignancy - Mei Nakamura; Yumiko Ishizuka; Yoshiya Horimoto; Akihiko Shiraishi; Atsushi Arakawa; Naotake Yanagisawa; Kotaro Iijima; Mitsue Saito (Breast, 2020)
Background: Mammography (MG) is widely used for screening examinations. Dense breast reduces MG screening sensitivity, possibly delaying diagnosis. However, little is known about the characteristics of breast cancers without MG findings indicative of malignancy. Hence, we investigated breast cancer patients with tumors not detected by MG. Patients and methods: In total, 1758 Japanese patients with breast cancer, undergoing curative surgery between 2012 and 2018 without neo-adjuvant chemotherapy, were retrospectively investigated. Clinicopathological features were compared between patients without (MG-negative) and with (MG-positive) cancer-specific findings on MG. The current study included cases who came to our hospital after experiencing subjective symptoms, or whose tumors were detected by MG and/or US-screening. We reviewed results of both MG and US conducted at our institution. Results: There were 201 MG-negative cases (11.4%). In patients with invasive disease, multivariate analysis revealed MG-negative patients to have higher breast density on MG (p < 0.001). Tumors of MG-negative patients were smaller (p < 0.001), showed less lymph node involvement (p = 0.011), and were of lower grade (p = 0.027). The majority of MG-negative tumors were found by ultrasound screening, being smaller than tumors in patients with subjective symptoms. In the MG-negative group, tumor characteristics such as tumor grade did not differ between those detected by screening versus subjective symptoms. Conclusion: Most tumors in MG-negative group patients were identified by US screening and the diseases were found at early stages with low malignancy. The usefulness of additional ultrasound with MG-screening might merit further investigations.